PATIENT’S PERCEPTION TOWARDS ALLOPATHIC AND AYURVEDIC MEDICINES IN INDIA: AN EMPIRICAL STUDY - NAWAZ KHAN, AHMED; NAWAZ KHAN, AHMED (International Journal of Psychosocial Rehabilitation, 2021)
The main objective of this article is to understand the prevalence and perception among Indian patients towards traditional Indian medicines as well as their notions regarding allopathic medicines on its feasible integration. Changing lifestyles and reduction in the affordability regarding sick care, in terms of money and time are some of the factors that are leading patients towards helping them to think about their wellbeing. Many patients also suggested that due to lack of curative treatment for several chronic illnesses excessive cost of allopathic medicines, microbial resistance, and its emerging diseases amongst them are some of the reasons for them to shift towards traditional or alternative medications in India. A cross-sectional study was undertaken during this research to analyse different perspectives related to ayurvedic and allopathic but will also discuss why all around the globe are still very much aware about Ayurveda. This study showed considerable support on behalf of both traditional and allopathic but also significant variation among its users. Still, Ayurvedic medicines is increasing its popularity all around the world, but patients are more concerned about their quality through inclusion of advanced technology to gain global acceptance over allopathic medicines.